Teacher’s Feedback to Improve Students’ Writing Recount Text at First Semester Students of English Letters Department UIN Raden Mas Said Surakarta in 2024-2025 - Cahyono, Dwi; Ayuningtyas Palupi, Risqi Ekanti; Sunardi, Andhina Ika (Universitas Muhammadiyah Ponorogo, 2025)
This research aims to improve the students’ writing skill through Teacher Feedback strategy at First Semester Students of English Letters Department UIN Raden Mas Said Surakarta in 2024-2025. The subjects of this research were 27 students of A class. This research used a cycle of Classroom Action Research, and it consisted of five meetings. The CAR cycle contents are Planning, Acting, Observing, and Reflecting. This research used two types of data, and they were qualitative and quantitative data. The qualitative data were obtained through observations during the teaching learning activities. Moreover, the quantitative data were the scores of the students’ writing recount text before the implementation of the Feedback (pre-test) and after the implementation of the Feedback (post-test). The students’ pre-test scores showed that the total was 1250. In this degree, the mean that the researcher gained in students’ pre-test score was 46.30. Furthermore, the students’ post-test scores showed the total was 2062. In this degree, the mean that the researcher gained in students’ post-test was 76.37. It can be seen that there was an improvement on students’ mean scores. Most of the students’ scores were increased from the pre-test and the post-test scores. It was from 29.63% (8 students) who passed the minimum score to 81.48% (22 students) of the 27 students. It can be seen that there was a significant improvement from the percentage before and after treatments. In short, applying Teacher Feedback strategy in teaching learning process can significantly improve the writing skills of the students.